Kontroversi dan Implikasi KUHP Baru Tahun 2026 terhadap Kebebasan Sipil di Indonesia - Febrianto Febrianto; Moh. Lubsi Tuqo Romadhan (Lembaga Yasin AlSys, 2026)
The enactment of the Kitab Undang-Undang Hukum Pidana (KUHP) through Law Number 1 of 2023, which will become effective in 2026, is positioned as a milestone in the decolonization of criminal law and the reform of the national legal system, yet it simultaneously generates serious controversy regarding its implications for civil liberties and the protection of human rights in a democratic state governed by the rule of law. This study aims to analyze the normative controversies embedded in the new 2026 KUHP and to examine their implications for civil liberties from the perspective of the rule-of-law state and human rights. The research employed a normative juridical method with statutory, conceptual, and human rights approaches. Legal materials were analyzed descriptively-analytically and prescriptively through normative interpretation based on the principle of legality, the principle of proportionality, and the protection of constitutional rights. The findings indicate that several provisions in the new KUHP, such as the renewed regulation of criminal defamation against the President and state institutions, the dissemination of false information, and the criminalization of aspects of morality and private life still contain broadly framed and multi-interpretable norms that risk expanding criminalization of critical expression, restricting freedom of opinion, and opening space for state intervention in the private sphere. At the level of practice (law in action), this condition may produce a chilling effect, broaden the discretion of law enforcement authorities, and ultimately undermine the quality of democracy and civil liberties. Therefore, the implementation of the new KUHP requires progressive interpretation by law enforcement officials, effective public oversight, and ongoing normative evaluation to ensure conformity with the principles of a democratic rule-of-law state and international standards of human rights protection.